O zbawieniu (z Wierszy ostatnich Czesława Miłosza) - Marek Bernacki (Postscriptum Polonistyczne)
The article is dedicated to detailed analyzing and interpreting the Miłosz’s poem O zbawieniu [On salvation]. This poem was most probably written two years before Miłosz’s death and was located at the end of the volume Last Poems (2006). The author confronts “the last poem” of Miłosz with Mickiewicz’s “the cry poem” written in Lausanne (“wiersz płacz” as Przyboś called it): “I shed pure tears, countless tears…”. Both poems – though representing different genres – (Mickiewicz’s poem is a model example of immediate lyrical confession; Miłosz’s poem has a form of poetic minitreaty) express related ideas through similar figures such as: repetition, enumeration, synecdoche, ellipse. Both texts can be related not only because of the similarities in composition and structure, but also because of their catharsisaimed character. Mickiewicz achieves purification through tears shed over his life and humble acceptance of the fact that a project formed in his youth resulted in a disaster in his manhood. Miłosz presents the state of liberating salvation as a result of the peaceful and lighted with nonofthisworld gleam contemplation of the difficult truth concerning the necessity of giving up all the earthly things. Both “last poems” of the great poets can be regarded as the masterpieces of a lyric of vanitas. Their main aim can be described as an attempt to confront the mystery of eschatological dimension of human existence.